2013
DOI: 10.1039/c2sm26393a
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic wetting and de-wetting of drops on substrates patterned with polygonal posts

Abstract: Table of contentWe record contact line motion of ink-jet printed drops spreading and evaporating on surfaces patterned with polygonal microposts and, aided by lattice Boltzmann simulations, explain the drop shapes in terms of interface pinning at posts. AbstractWe present results showing how water drops, produced by ink-jet printing, spread on surfaces patterned with lattices of diamond or triangular posts. Considering post widths typically ~7 m and lattice spacings between 15-40 m, we observe drop shapes with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 48 publications
(60 reference statements)
1
35
0
Order By: Relevance
“…patterns composed of several primary directions, as it has been done by Vrancken et al [18]. Hence, the authors managed to obtain droplets adopting polygonal-like footprints.…”
Section: Introductionmentioning
confidence: 91%
“…patterns composed of several primary directions, as it has been done by Vrancken et al [18]. Hence, the authors managed to obtain droplets adopting polygonal-like footprints.…”
Section: Introductionmentioning
confidence: 91%
“…The contact angle of the liquid with both the posts and the substrate is θ which we vary in the range 30 o to 70 o . This range is representative of different hydrophilic material, for example the polymers considered in[1] or [16].…”
Section: B Geometrymentioning
confidence: 99%
“…Jokinen et al [24] developed a method of fabricating irregular pillars on a square array surface, and found directional wetting property of droplets on this surface, where droplets spread to irregular square-like shapes. and Vrancken et al [7] reported the droplet shapes depend on the array geometry, pillar shape and array space. In previous studies, the researchers focused on the final shapes of droplets on lyophilic pillar-arrayed surfaces, while the evolution of the projected shape from an initial circle to a final polygon is essentially a dynamic process.…”
Section: Introductionmentioning
confidence: 99%
“…Spreading of a droplet on a micro-structured surface is prevalent in nature, [1,2] and is of key importance in a wide range of applications, such as DNA technologies, [3,4] fog-harvesting, [5,6] inkjet printing, [7][8][9] biomedicine [10,11] and microfluidics. [12,13] To develop these practical applications, dynamic wetting behaviours of a droplet on a textured surface have been investigated extensively in recent years.…”
Section: Introductionmentioning
confidence: 99%